Honey bee colony winter loss rates for 35 countries participating in the COLOSS survey for winter 2018–2019, and the effects of a new queen on the risk of colony winter loss. Issue 5 (19th October 2020) - Gray, Alison; Adjlane, Noureddine; Arab, Alireza; Ballis, Alexis; Brusbardis, Valters; Charrière, Jean-Daniel; Chlebo, Robert; Coffey, Mary F.; Cornelissen, Bram; Amaro da Costa, Cristina; Dahle, Bjørn; Danihlík, Jiří; et al.
Abstract : This article presents managed honey bee colony loss rates over winter 2018/19 resulting from using the standardised COLOSS questionnaire in 35 countries (31 in Europe). In total, 28, 629 beekeepers supplying valid loss data wintered 738, 233 colonies, and reported 29, 912 (4.1%, 95% confidence interval (CI) 4.0–4.1%) colonies with unsolvable queen problems, 79, 146 (10.7%, 95% CI 10.5–10.9%) dead colonies after winter and 13, 895 colonies (1.9%, 95% CI 1.8–2.0%) lost through natural disaster. This gave an overall colony winter loss rate of 16.7% (95% CI 16.4–16.9%), varying greatly between countries, from 5.8% to 32.0%. We modelled the risk of loss as a dead/empty colony or from unresolvable queen problems, and found that, overall, larger beekeeping operations with more than 150 colonies experienced significantly lower losses ( p < 0.001), consistent with earlier studies. Additionally, beekeepers included in this survey who did not migrate their colonies at least once in 2018 had significantly lower losses than those migrating ( p < 0.001). The percentage of new queens from 2018 in wintered colonies was also examined as a potential risk factor. The percentage of colonies going into winter with a new queen was estimated as 55.0% over all countries. Higher percentages of young queens corresponded to lower overall losses (excluding losses from natural disaster), but also lower losses from unresolvable queen problems, and lower losses from winter mortality ( p < 0.001). Detailed results for each country and overall are given in a table, and a map shows relative risks of winter loss at regional level.